Pengaruh Sintering Serbuk Batuan Basalt sebagai Bahan Penguat pada Komposit Polyester terhadap Sifat Fisik dan Mekanik - Hendronursito, Yusup; Saputra, Asep Andri; Rajaguguk, Tumpal Ojahan; Sumardi, Slamet; Supriyatna, Yayat Iman; Isnugroho, Kusno; Birawidha, David Candra; Amin, Muhammad (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2021)
Basalt rock has great potential in Lampung Province but is only used as a building construction material. Basalt has superior characteristics such as abrasion/wear resistance, compressive strength and chemical reaction resistance making it suitable as a filler or reinforcement for composites. This study aims to determine the effect of basalt rock powder sintering as a reinforcing filler on the mechanical and physical properties of polymer matrix composites. The parameters used included variations in sintering temperature: 8500C, 9500C, and 1.0500C, variations in particle size: 100 < X < 150 mesh, 150 < Y < 200 mesh and 200 < Z < 270 mesh, and the volume fraction comparison of basalt sintering powder and polyester resin. 70: 30%, 80: 20%, and 90: 10%. The experimental design uses the L9 3^3 taguchi orthogonal array run 9 specimens. Taguchi analysis shows that the parameters that affect the mechanical and physical properties are the sintering temperature. sintering temperature contributed 61.77% to wear, and 87.58% to compressive strength, and 95.32% to composite density. The experimental results with the best value obtained a wear value of Â 0.235 x 10-7mm2 / kg, a compressive strength of 118.873 MPa, and a density of 2.272 gr/cm3.